The Stalin affair : the impossible alliance that won the war - Milton, Giles (Henry Holt and Company, 2024)
"From international bestselling historian Giles Milton comes the remarkable true story of the motley group of allied men and women who worked to manage Stalin's mercurial, explosive approach to diplomacy during four turbulent years of World War II. In the summer of 1941, Hitler did the unthinkable-he invaded the Soviet Union, shattering what Stalin had until then considered an ironclad partnership. It was a shocking, urgent turning point in the war, in the wake of which a team of British and American men and women were assembled with one central goal: to keep the Red Army fighting on the Eastern Front. There were real fears that Stalin's forces would either be defeated (as looked increasingly likely as Hitler's army pushed forward at a merciless pace) or that the Soviet leader would once again strike a deal with Hitler. Either eventuality would spell catastrophe for both Britain and America. Hitler would be able to concentrate his vast military resources in Western Europe, making the continent's ultimate liberation virtually impossible. Enter Averell Harriman: a railroad magnate, and, at the start of the war, the fourth richest man in America. At Roosevelt's behest he traveled to Britain to serve as a liaison between him and Churchill and spearhead what became known as the Harriman mission. Together with his fashionable young daughter Kathy, an unforgettable cast of British diplomats, and Churchill himself, he managed to wrangle Stalin into the partnership the allies needed to finally defeat Hitler. Based on unpublished diaries, letters and secret reports, The Stalin Affair reveals troves of new material about the path to Allied victory, full of vivid scenes between celebrated and infamous World War II figures. Ultimately, it provides fascinating, richly nuanced portrait of one of history's most complicated and notorious dictators"--